2007
DOI: 10.1016/j.jadohealth.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to a Concept for Physician Intervention in Adolescent Alcohol Use

Abstract: Purpose-This study was designed to understand adolescent and parental perceptions, receptivity, and reactions to the concept of screening and brief intervention that primary care physicians can use to reduce alcohol consumption by their non-alcohol dependent adolescent patients.Methods-A total of 6 nation-wide computer-assisted telephone focus groups were conducted; 3 with low-to-moderate risk for alcohol problems adolescents aged 15-17 years and 3 with parents of such adolescents.Findings-Parents and adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Research has shown that young adults are willing to talk about their cigarette, marijuana, and alcohol use and participate in interventions to reduce such use (e.g., Stern et al, 2007; Yoast, Fleming, and Balch, 2007; Baggett and Rigotti, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that young adults are willing to talk about their cigarette, marijuana, and alcohol use and participate in interventions to reduce such use (e.g., Stern et al, 2007; Yoast, Fleming, and Balch, 2007; Baggett and Rigotti, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…51 All of these models have been modestly successful in showing reductions in substance use and related consequences and/ or risky behaviors, although 1 trial found similar substance use reductions in both experimental and control groups. 50 Physicianimplemented BI is acceptable to both teenagers 16 and clinicians. 52 Although a recent US Preventive Services Task Force 53 review found insufficient scientific basis to recommend any particular BI for addressing adolescent substance use, this clinical report reviews the current literature base to summarize expert opinion about practical BI strategies.…”
Section: Brief Interventionmentioning
confidence: 99%
“…15 Adolescents consider physicians an authoritative source of knowledge about alcohol and drugs and are receptive to discussing substance use. 16 These findings underscore the tremendous opportunity for addressing substance use in primary care settings, the medical home, and other settings in which children and adolescents receive medical care and health advice.…”
Section: Introductionmentioning
confidence: 96%
“…Adolescents and their families are receptive to screening and intervention in medical settings, and in fact perceive the quality of care to be higher when SU is addressed [47, 48]. This may be especially salient for ethnic groups or populations for whom these conditions are particularly stigmatized or who are less likely to seek specialty psychiatric or SU treatment [49].…”
Section: Su and Adolescent Healthmentioning
confidence: 99%